2008
DOI: 10.1017/s0007114508944123
|View full text |Cite
|
Sign up to set email alerts
|

β-Cryptoxanthin from supplements or carotenoid-enhanced maize maintains liver vitamin A in Mongolian gerbils (Meriones unguiculatus) better than or equal to β-carotene supplements

Abstract: Maize with enhanced provitamin A carotenoids (biofortified), accomplished through conventional plant breeding, maintains vitamin A (VA) status in Mongolian gerbils (Meriones unguiculatus). Two studies in gerbils compared the VA value of b-cryptoxanthin with b-carotene. Study 1 (n 47) examined oil supplements and study 2 (n 46) used maize with enhanced b-cryptoxanthin and b-carotene. After 4 weeks' depletion, seven or six gerbils were killed; remaining gerbils were placed into weight-matched groups of 10. In st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 37 publications
9
72
1
Order By: Relevance
“…2 However, animal studies have shown that β-cryptoxanthin is absorbed and stored in many tissues 16 and it maintains the vitamin A status of gerbils as efficiently or better than β-carotene. 17 Most of the yellow maize grown and consumed throughout the world has less than 2.0 μg/g DW of provitamin A carotenoids in kernels. 2 The first wave of biofortified maize grown in Zambia contained 7.5 to 10.3 μg/g DW BCE and higher levels of β-cryptoxanthin, which is as efficient as β-carotene as a source of vitamin A.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2 However, animal studies have shown that β-cryptoxanthin is absorbed and stored in many tissues 16 and it maintains the vitamin A status of gerbils as efficiently or better than β-carotene. 17 Most of the yellow maize grown and consumed throughout the world has less than 2.0 μg/g DW of provitamin A carotenoids in kernels. 2 The first wave of biofortified maize grown in Zambia contained 7.5 to 10.3 μg/g DW BCE and higher levels of β-cryptoxanthin, which is as efficient as β-carotene as a source of vitamin A.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The beauty of breeding staple crops with provitamin A carotenoids is that the body will offer a line of protection from hypervitaminosis A due to the regulatory mechanisms in place during the bioconversion of provitamin A carotenoids to retinol [41]. Maize has been biofortifi ed with both β-carotene and β-cryptoxanthin [42,43]. On a mass basis, these two provitamin A carotenoids have similar bioeffi cacy [42,43].…”
Section: Methods To Improve Global Vitamin a Statusmentioning
confidence: 99%
“…Maize has been biofortifi ed with both β-carotene and β-cryptoxanthin [42,43]. On a mass basis, these two provitamin A carotenoids have similar bioeffi cacy [42,43]. Biofortifi ed maize genotypes have been fed to Zambian children with quick adaptation periods [44,45].…”
Section: Methods To Improve Global Vitamin a Statusmentioning
confidence: 99%
“…Yellow maize has been shown to be rich in beta carotenes, a primary precursor of vitamin A [11]. This food crop has been found to have a high potential to maintain the hepatic reserves of retinol in animals [12] [13]. Supplementation with the yellow variety of maize, a staple in this region of Cameroon can go a long way to alleviate VAD.…”
Section: Introductionmentioning
confidence: 99%